Utilizing Wasteaware Benchmark Indicators to Improve Municipal Solid Waste Management in Northern Thailand - Vassanadumrongdee, Sujitra; Kallayanapattharasit, Ridthipat; Lekkham, Arisara; Unroj, Pattayaporn (Applied Environmental Research, 2023)
Primarily responsible for waste collection and disposal, local governments in northern Thailand face significant obstacles in managing waste. Mixing infectious, hazardous and general waste, over-utilizing incinerators and implementing environmentally improper disposal methods all contribute to burgeoning volumes of waste with adverse environmental and health impacts. The objectives of this study are to use the Wasteaware benchmark indicators (WABIs) to assess the effectiveness and sustainability of the waste management of Wiengthoeng Sub-district Municipality (WSM), to identify advantages and disadvantages of its system and offer fact-based recommendations for improvement. Pertinent data was obtained through interviews of governmental authorities, community members and private sector employees between October, 2020 and May, 2021 using designed questionnaires and through review of official governmental records. It was found that with the help of village leaders, increased public participation in MSWM and working with local governments resulted in more widespread involvement in the 3Rs practices. Economic measures facilitated the objectives. Assessing ‘pay-as-you-throw’ fees resulted in a focus on lowering household costs through waste separation and reduction. The financial benefits of the program were not significant, but the source waste required for final disposal was reduced. The findings suggest that to increase the sustainability of municipal solid waste management, source reduction and segregation should be promoted to minimize the volume of refuse sent to landfills. Source reduction and collaboration between residents and village leaders can provide more long-term benefits than positive short-term economic impacts. Moreover, to improve the sustainability of its physical assets, WSM must better address the environmental impact of waste treatment and disposal.